O Sentido Do Trabalho Escolar Para O Adolescente Em Cumprimento De Medida Socioeducativa De Internação - Carvalho, Valeria Regina Valerio De [UNIFESP] (2017)
The subject of this research is the relation of the student with the schooling process. The aim is to understand the meaning of the school work developed at Fundação CASA (Centro de Atendimento Socioeducativo ao Adolescente). From the perspective of the adolescent, author of infrational act, in fulfillment with socio-educational measure of internment. It is intended to problematize about the relationship that these adolescents stablish with the school, through the analysis of their previous trajectories until the current school situation experienced at Fundação CASA. The research data has been collected through interviews semi-structured carried with six interned adolescents. The analyze was carried out based on the concepts of the student work, meaning of the school work and relation with knowledge, originating from theoretical reference of the authors Perrenoud (1995) and Charlot (2005). As research results, it is perceived, on the one hand, a truncated relationship of these young people with the school, prior to internment, whose trajectories were permeated by situations of abandonment, disapprovals and expulsions, and contradictorily, on the other hand, it was possible to evidence that, in some way, in the internment ambient, they stablish a new relationship with the school, that manifests positively, although it is also utilitarian.